Alterations of the Bile Microbiome in Recurrent Common Bile Duct Stone. (29th September 2020) - Ye, Cheng; Zhou, Wence; Zhang, Hui; Miao, Long; Lv, Gen
Abstract : Objective . Common bile duct stone (CBDS) recurrence is associated with bile microbial structure. This study explored the structure of bile microbiome in patients with recurrent CBDS, and its relationship with the recurrence of CBDS. Methods . Patients with recurrent CBDS (recurrence group) and controls without CBDS (control group) requiring endoscopic retrograde cholangiopancreatography (ERCP) were prospectively included. The control group was noncholelithiasis patients, mainly including benign and malignant biliary stenosis. Bile samples were collected, and bile microbiome structure was analyzed by the 16S rRNA encoding gene (V3–V4). Results . A total of 27 patients in the recurrence group and 19 patients in the control group were included. The diversity of bile microbiome in the recurrence group was significantly lower than that in the control group (Shannon index: 2.285 vs. 5.612, P = 0.001 ). In terms of bile microbial distribution, patients with recurrent CBDS had significantly higher Proteobacteria (86.72% vs. 64.92%, P = 0.037 ), while Bacteroidetes (3.16% vs. 8.53%, P = 0.001 ) and Actinobacteria (0.29% vs. 6.74%, P = 0.001 ) are significantly lower compared with the control group at the phylum level. At the genus level, the recurrence group was mainly the Escherichia, and there was a variety of more evenly distributed microbiome in the control group, with significant differences between the two groups. Conclusion . The diversity of bile microbiome in patients with recurrent CBDS is lower. Patients with recurrent CBDS may have bile microbial imbalance, which may be related to the repeated formation of CBDS.